2008
DOI: 10.1634/stemcells.2007-0117
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Reversal Within the Early Human Hematopoietic Compartment

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Our data show that there was no observed toxicity on this population of cells. This is consistent with the fact that these non-committed progenitors express very low levels of the TfR1/CD71 (Gross et al 1997; Knaan-Shanzer et al 2008; Lansdorp and Dragowska 1992). We have previously shown that the conjugate is toxic to late (committed) progenitor cells of both the erythroid and myeloid lineages (CFU-e, BFU-e and CFU-GM) (Daniels et al 2011) that are known to express the TfR1 (Daniels et al 2006b).…”
Section: Discussionsupporting
confidence: 87%
“…Our data show that there was no observed toxicity on this population of cells. This is consistent with the fact that these non-committed progenitors express very low levels of the TfR1/CD71 (Gross et al 1997; Knaan-Shanzer et al 2008; Lansdorp and Dragowska 1992). We have previously shown that the conjugate is toxic to late (committed) progenitor cells of both the erythroid and myeloid lineages (CFU-e, BFU-e and CFU-GM) (Daniels et al 2011) that are known to express the TfR1 (Daniels et al 2006b).…”
Section: Discussionsupporting
confidence: 87%
“…This colony was established with mice originally purchased from Jackson Laboratories (Bar Harbor, Me., USA). The mice were kept and housed as previously described [25]. All experimental procedures were approved by the local Experimental Animal Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the higher the expression of CD34 in a given HSPC subset is, the higher its efficacy both in an in vivo long‐term re‐populating assay (Krause et al ., ) and in clinical BM transplantation outcome (Beksac and Preffer, ). This can be explained either as the occurrence of a specific stem cell subpopulation within the CD34 high ‐HSPC pool or as a higher propensity of CD34 high ‐HSPC to reverse their pre‐commitment thereby recovering features of multipotent stem cells (Dooner et al ., ; Knaän‐Shanzer et al ., ; Puca et al ., ).…”
Section: Introductionmentioning
confidence: 99%